Sixth Grade Students' Some Difficulties and Misconceptions on Angle Concept - Deniz ÖZEN ÜNAL; Ömer ÜRÜN (Anı Publishing, 2021)
This study aims to determine the misconceptions and difficulties of sixth-grade students on the subject of angles. The study participants are 25 sixth grade students from a public school in a city in western Turkey during the 2017-2018 academic year. This qualitative study used 17 open-ended questions designed by the researchers for data collection to examine the students' misconceptions and difficulties. Data were examined by implementing content analysis. It has been analysed that students cannot define the angle due to difficulties and misconceptions in determining the corners and edges of a symbol. Besides, they also find it difficult to compare the measures of the angles, adjacent angles, complementary and supplementary angles.